1985
DOI: 10.4049/jimmunol.135.5.3151
|View full text |Cite
|
Sign up to set email alerts
|

Cellular tropism of the human retrovirus HTLV-III/LAV. I. Role of T cell activation and expression of the T4 antigen.

Abstract: In cultures of normal human lymphocytes infected with the human retrovirus HTLV-III/LAV, detectable cytoplasmic virus appears and then disappears in a proportion (1 to 10%) of cells, followed by release of virus detected by particulate reverse transcriptase activity, virus antigen assay, and infectivity titer. Virus infection is associated with loss of detectable T4 antigen on infected cells and, ultimately, complete loss of T4+ cells from the culture. Residual non-T4+ cells are not susceptible to a second inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 491 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The findings of the present study may, therefore, suggest that IL-31 plays a significant role in sexual transmission of HIV, rather than in the blood transmission of HIV, mainly via skin and mucous membranes. This inference is supported by the findings of most of the recent studies, which have reported the association of IL-31 levels with allergic diseases, spontaneous asthma, inflammatory bowel disease, and chronic urticarial [25,26,34] …”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…The findings of the present study may, therefore, suggest that IL-31 plays a significant role in sexual transmission of HIV, rather than in the blood transmission of HIV, mainly via skin and mucous membranes. This inference is supported by the findings of most of the recent studies, which have reported the association of IL-31 levels with allergic diseases, spontaneous asthma, inflammatory bowel disease, and chronic urticarial [25,26,34] …”
Section: Discussionsupporting
confidence: 65%
“…The present study also revealed significantly higher levels of IL-31 in patients infected through the sexual transmission of HIV compared to those infected through blood transmission ( P < .01). This could be because the mucosal immune system is the storehouse of activated CD4 + cells, [25] where HIV replicates further efficiently [26,27] . The CD4 + cells harbor IL-31, leading to increased cytokine concentrations in these cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations